2011
DOI: 10.1002/jez.697
|View full text |Cite
|
Sign up to set email alerts
|

Running in cold weather: morphology, thermal biology, and performance in the southernmost lizard clade in the world (Liolaemus lineomaculatussection: Liolaemini: Iguania)

Abstract: The integration or coadaptation of morphological, physiological, and behavioral traits is represented by whole-organism performance traits such as locomotion or bite force. Additionally, maximum sprint speed is a good indicator of whole-organism performance capacity as variation in sprinting ability can affect survival. We studied thermal biology, morphology, and locomotor performance in a clade of Liolaemus lizards that occurs in the Patagonian steppe and plateaus, a type of habitat characterized by its harsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 80 publications
(111 reference statements)
7
56
0
1
Order By: Relevance
“…A Panasonic SV200 camcorder set at 30framess -1 was mounted 61cm above the surface in all cases, and a segment of length 20cm was filmed, which related to a track distance of 0.45 to 0.65m. Previous studies on the speed performance of 10 species of Liolaemus showed that maximum speed was obtained at a distance between 0.45 and 0.60m from the starting point (Bonino et al, 2011). Additionally, the speed values obtained here are similar to those obtained by Bonino and colleagues, who used a racetrack with lightemitting diode sensors and an electronic timer.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…A Panasonic SV200 camcorder set at 30framess -1 was mounted 61cm above the surface in all cases, and a segment of length 20cm was filmed, which related to a track distance of 0.45 to 0.65m. Previous studies on the speed performance of 10 species of Liolaemus showed that maximum speed was obtained at a distance between 0.45 and 0.60m from the starting point (Bonino et al, 2011). Additionally, the speed values obtained here are similar to those obtained by Bonino and colleagues, who used a racetrack with lightemitting diode sensors and an electronic timer.…”
supporting
confidence: 86%
“…Additionally, we explored whether there is a tradeoff between clinging ability and speed in these Liolaemini lizards using equivalent types of substrates. Considering the many previous results that relate morphology and ecological traits in the same lizard group (Jaksic et al, 1980;Schulte et al, 2004;Fernandez et al, 2011;Tulli et al, 2009;Tulli et al, 2011b;Bonino et al, 2011), we predicted that the morphological traits would be better explained by phylogeny. By contrast, because habitat structure might influence locomotor performance, it was reasonable to expect that lizard species would show better performance on a racetrack that mimics their own habitat structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Las especies de Liolaemus parecen estar adaptadas a temperaturas ambientales bajas (Cruz et al 2005;Rodríguez-Serrano et al 2009;Fernández et al 2011;Medina et al 2012;Moreno Azócar et al 2013), tanto por su relación con los valores medios de Tc como en los de TCmín (Cruz et al 2005;Bonino et al 2011, Moreno Azócar et al 2013). …”
Section: Discussionunclassified